(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Guillain-Barre Syndrome (GBS) is a common cause of acute flaccid paralysis (AFP) in children globally, and in the advanced world it has emerged as the commonest cause of AFP after eradication of poliomyelitis Objectives: Objective of the study was to find out frequency of respiratory failure and factors contributing to respiratory failure in cases of GB syndrome. Study Design: It is a prospective descriptive study. Patients and Methods: Detailed account of patients presenting with diagnosis of G.B. syndrome was recorded in pre-designed proforma. This study was conducted over a period of 06 months in Department of Paediatrics Children’s Hospital & The Institute of Child Health, Lahore. Statistical analysis was done using SPSS 14. Results: There were a total of 110 patients with age range of 05 to 15 years.43.6% were male and 56.4% were female. 26.4% developed respiratory failure, out of them 48.3% had bulbar involvement and 62.1% had autonomic involvement. Out of 81 patients who did not develop respiratory failure only 25.9% had bulbar involvement and 34.6% had autonomic involvement. A p value of 0.018 for autonomic dysfunction and 0.047% for bulbar involvement was found. Both p values are significant. Conclusion: Bulbar involvement and autonomic dysfunction are contributory factors for respiratory failure in cases of severe GBS. Addressing these factors can bring an improvement in management.